2015
DOI: 10.1186/s13104-015-1358-7
|View full text |Cite
|
Sign up to set email alerts
|

Reducing episodes of diabetic ketoacidosis within a youth population: a focus group study with patients and families

Abstract: BackgroundDiabetic ketoacidosis (DKA) is the most common cause of morbidity and mortality for youth with type 1 diabetes mellitus (T1DM). This article reports qualitative data from focus groups with youth and parents of youth with T1DM on the barriers that they identify to DKA prevention and resources that may aid youth better manage their diabetes.MethodsFour focus groups were held in three communities, two rural and one urban, in the Canadian province of Newfoundland and Labrador (NL) with adolescents and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
5
0
3
Order By: Relevance
“…Many barriers are known leading to delay in diagnosing DKA. Of those, there are difficulty in distinguishing cases of DKA from other illnesses, information overload, and ling period from initial diagnosis [ 16 ]. Such barriers remain a major obstacle in prevention of DKA in children even in developed countries with active prevention campaigns [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many barriers are known leading to delay in diagnosing DKA. Of those, there are difficulty in distinguishing cases of DKA from other illnesses, information overload, and ling period from initial diagnosis [ 16 ]. Such barriers remain a major obstacle in prevention of DKA in children even in developed countries with active prevention campaigns [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crossen et al[25] concluded that signs of impending DKA were seen in children with type I diabetes who had recent emergency department visits and had infrequent subspecialty primary care visits. Chafe et al[26] utilized a focus study group of patients and families to identify ways to reduce episodes of DKA in the youth population. This project identified factors that put the youth at increased risks and recognized areas to improve those odds.…”
Section: Discussionmentioning
confidence: 99%
“…Terdapat beberapa faktor yang meningkatkan resiko terjadinya ketoasidosis pada penderita diabetes yaitu : perbedaan informasi tentang diabetes yang diterima, banyaknya informasi tentang keadaan penyakit yang diterima, lamanya menderita penyakit, informasi yang berlebihan tentang kondisi penyakit, keadaan geografis daerah tempat tinggal, kurangnya akses terhadap tenaga kesehatan spesialis, serta beban psikologis yang dialami oleh remaja yang dirawat oleh keluarga selain orang tua. (Chafe, et al 2015). Anak dengan DM tipe 1 yang tidak tinggal atau tidak dirawat langsung oleh orang tua memiliki kecenderungan mengalami komplikasi berupa KAD (Usher-Smith Et al, 2011).…”
Section: Pendahuluanunclassified
“…Dukungan dari masyarakat sekitar, informasi baru tentanga KAD, telpon seluler, informasi yang tepat dan ringkas bagi pihak sekolah dan keluarga/wali serta set kelengkapan perawatan KAD untuk orang tua dapat membantu meningkarkan menejemen diabetes mellitus tipe 1 dan mencegah serangan KAD berulang. Selain itu ketidakpatuhan menejemen terapi insulin juga menjadi faktor penyebab terjadinya KAD (Chafe et al, 2015)…”
Section: Pendahuluanunclassified